Mechanical Properties Of Thixoformed Al-5Si Alloy Composite Reinforced By Multiwalled Carbon Nanotubes And Alumina Powder - Salleh, Mohd Shukor; Yahaya, Saifudin Hafiz; Mohamad, Noraiham; Hashim, Hanizam; Omar, Mohd Zaidi (Penerbit Akademia Baru, 2020)
Carbon nanotubes (CNT) as reinforced particles in aluminium matrix composites have been an interesting exploration in recent years. Some research combined CNT with ceramic materials as dual reinforcements in the aluminium matrix to enhance further the mechanical strength of the composite. However, the effects of some fabrication processes on the tube structural integrity of CNT are rather limited. This study is to determine the effects of single and dual reinforcements in Al5Si alloy on the mechanical properties of the composites. The reinforcement particles were predistributed by using a ball milling process through powder metallurgy. The mixed was green compacted into a pallet form before injected into a molten Al5Si alloy matrix. The molten composite was stirred before pouring into a permanent mould via a cooling slope. Next, the cast billet was subjected to thixoforming and T6 heat treatment processes. According to the comparison results of the pre-distributed reinforcements, the integrity of CNT structure in dual reinforcements was destroyed due to excessive milling from Al2O3 particles. There was no significant change of microstructures evolution and grain sizes of both composites after the thixoforming and T6 heat treatment. The yield strength, ultimate tensile strength and elongation to fracture of single reinforcement obtained were 316 MPa, 347 MPa, and 13.3%, respectively and much superior than the dual reinforcements. These results show that maintaining the tube structure of CNT is very critical for mechanical strength enhancement through load transfer mechanism of the CNT-Al5Si alloy composite